Can macrophages within the microenvironment of locally invasive rectal cancers predict response to radiotherapy?. (26th February 2015) - Shaikh, Shafaque; Noshirwani, Arish; West, Nicholas; Perry, Sarah; Jayne, David
Abstract: Background: Only half of patients with locally invasive rectal carcinoma respond to short-course preoperative radiotherapy. A predictive test enabling better patient selection could avoid unneccessary radiation exposure to poor responders. Macrophages within the tumour immune microenvironment with tumoricidal M1 and tumour-protective M2 phenotypes could be modulating this response. This study investigated the possible predictive value of M1 and M2 subpopulations in identifying patients' likely response to short-course preoperative radiotherapy. Methods: Biopsy samples were taken from 29 patients with locally invasive rectal carcinoma before treatment with short-course radiotherapy and surgical specimens obtained after resection following short-course preoperative radiotherapy. Dual-staining immunohistochemistry was performed with CD68 as macrophage marker, HLA-DR as M1 marker, and CD163 as M2 marker. Samples were scored for hot-and-random spots by Nuance software (version 3.0.2) and compared with patients' outcome data. Tumour response was measured by assessment of reduction of tumour-cell density. Findings: Samples revealing a low score for HLA-DR positive M1 macrophages exhibited a better response to short-course radiotherapy with up to 80% (median 80·38% [IQR 46·94–84·73]) reduction in the tumour cell density. On the other hand those with a high score exhibited a poor response with only up to 20% (20·26 [0–48·19]) reduction. The difference in response between the two groups was significant (p=0·017). No such trends were observed for CD163+ M2 macrophages. The ratio of HLA–DR+ to CD163+ macrophages for biopsy and resection samples was significantly different, showing a drop in the HLA-DR positive macrophages in the resection samples (p=0·024). The mean of the difference between the biopsy (median 2·53 [IQR 1·98–3·08]) and resection (1·38 [0·96–1·8]) was 1·15 (p=0·024). Interpretation: Patients with a variable macrophage phenotype composition within biopsy samples from patients with locally invasive rectal carcinoma respond differently to short-course preoperative radiotherapy. Further investigation involving a panel of macrophage and other immune-cell markers could verify and validate these findings and develop them as predictive tests identifying good responders to radiotherapy in patients with locally invasive rectal carcinoma. Funding: None.